2009
DOI: 10.1017/s1368980008001997
|View full text |Cite
|
Sign up to set email alerts
|

Association of BMI and nutritional habits with hypertension in the adult population of Croatia

Abstract: Objective: The purpose of the present study was to investigate the distribution of hypertension, its nutritional and other determinants and their association in Croatia. Design: Population-based, cross-sectional study. Setting: Croatia. Subjects: Representative random sample of 9070 adults (18 years and older) from all Croatian regions, selected using multistage sampling. Results: Overall prevalence of hypertension (arterial blood pressure $140/ 90 mmHg) in Croatia was 45?5 %, of which 40 % were newly diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…A recent survey carried out in a large Croatian adult sample also failed to highlight such an association [38]. This could be explained by underestimation of salt intake, as we used selfreported data, or by a low variability in population.…”
Section: Diet and Blood Pressurementioning
confidence: 55%
“…A recent survey carried out in a large Croatian adult sample also failed to highlight such an association [38]. This could be explained by underestimation of salt intake, as we used selfreported data, or by a low variability in population.…”
Section: Diet and Blood Pressurementioning
confidence: 55%
“…Furthermore, hypertension is one of the most important health problems because of its relation to ischemic heart disease, which is the leading cause of death [2]. The prevalence of hypertension is 8-14% in population, worldwide [3].…”
Section: Introductionmentioning
confidence: 99%
“…High blood pressure and its complications is a significant problem and cardiovascular diseases are the most common cause of death in Iran [5]. Many of studies on different populations have identified certain factors such as older age, hypercholesterolemia, diabetes mellitus and increased body mass as being associated with high blood pressure [2,6,7]. The last years, some researchers have documented an increase in the risk of cardiovascular disease in subjects with systolic blood pressures (SBP) between 120 – 139 mmHg and/or diastolic blood pressures (DBP) between 80 – 89 mmHg [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…There was also a significant decrease in systolic blood pressure only in the control group, while no change was observed in urinary salt excretion level (Table ). While the reason for this is unclear, we believe that some other factors besides nutritional intake, such as body weight, age, nutritional elements, a particular food item, physical activity, or other lifestyle factors were involved …”
Section: Discussionmentioning
confidence: 99%
“…The relationship between blood pressure and salt intake is complicated. Some reports showed no relationship, and that blood pressure is influenced by BMI and age rather than salt intake . Even in the DASH‐Sodium trial, where participants' salt intake or body weight were kept constant during the intervention period, it was observed that complex factors, such as measurement variables or environmental or behavioral stress, influenced participants' blood pressure .…”
Section: Discussionmentioning
confidence: 99%